Risky environment: How extreme weather conditions in Nigeria lead to harvest failure - Julius Berger (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2024)
This paper investigates the relationship between extreme weather conditions and the risk of flooding-induced harvest failure in Nigerian agriculture using a probit model. I use household-level survey and gridded weather data to exploit weather variation across time and space. Risk of harvest failure increases for agricultural households with more extreme weather conditions. The effect is especially pronounced for a subsample of households in high-risk areas. Overall, extreme weather conditions more than double the risk of flooding-induced harvest failure. Educational attainment acts as a resilience strategy by enabling individuals to shift into other economic sectors and actively choose a less risky location of residence. Internet access per se does not seem to have a significant impact.
Keywords: Q12; Q54; I25; D83; N57; 330; Flooding Risk; Nigeria; Agriculture; Resilience Strategy; Education; Communication